2016
DOI: 10.1152/jn.00952.2015
|View full text |Cite
|
Sign up to set email alerts
|

New evidence of corticospinal network modulation induced by motor imagery

Abstract: Grosprêtre S, Lebon F, Papaxanthis C, Martin A. New evidence of corticospinal network modulation induced by motor imagery. J

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 60 publications
4
58
0
Order By: Relevance
“…Indeed, post‐synaptic modulation of motoneuronal responsiveness would have led to both conditioned and test H‐reflex increase (Grosprêtre et al . ). In fact, animal experiments have shown that the activation threshold of such spinal interneurons is lower than that of the motoneurons (Daniele & MacDermott, ), allowing them to be more sensitive to small stimuli such as the minor cortical output generated by MI.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Indeed, post‐synaptic modulation of motoneuronal responsiveness would have led to both conditioned and test H‐reflex increase (Grosprêtre et al . ). In fact, animal experiments have shown that the activation threshold of such spinal interneurons is lower than that of the motoneurons (Daniele & MacDermott, ), allowing them to be more sensitive to small stimuli such as the minor cortical output generated by MI.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, we demonstrated here that MI impacted specific spinal structures with lower level of excitability, as previously suggested (Grosprêtre et al . ). Accordingly, we found an increase in both conditioned H‐reflexes during MI, reflecting the modulation of presynaptic inhibition level, mediated by an interneuronal network.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations